Current perspective on diagnosis, epidemiological assessment, prevention strategies, and potential therapeutic interventions for severe acute respiratory infections caused by 2019 novel coronavirus (SARS-CoV-2) - Komal Rizwan; Tahir Rasheed; Shakeel Ahmad Khan; Muhammad Bilal; Tahir Mahmood (Taylor & Francis Group, 2020)
Coronaviruses are single-stranded RNA viruses that cause severe respiratory, enteric, and systemic infections in a vast range of hosts, including man, fish, mammals, and avian. Scientific interest has heightened on coronaviruses after the emergence of the 2019 novel Coronavirus (SARS-CoV-2). This review provides current perspectives on morphology, genetic diversity, transmission characteristics, replication cycle, diagnostic approaches, epidemiological assessment, and prevention strategies against the SARS-CoV-2. Moreover, different potential biotherapeutics such as small drug molecules, different vaccines, and immunotherapies to control severe acute respiratory infections caused by 2019 novel coronavirus (SARS-CoV-2) are repurposed and discussed with different mechanistic approaches. The current growth trends of the SARS-CoV-2/COVID-19 outbreak globally and preventive measures are briefly discussed. Furthermore, the lessons learned from the COVID-19 outbreak, so far, concluding remarks and future directions for controlling for COVID-19, are also recommended for a safer tomorrow.